6 Material Culture and Diasporic Experiences: A Case of Medieval Hanse Merchants in the Baltic. Issue 1 (September 2015) - Naum, Magdalena; Overholtzer, Lisa; Robin, Cynthia
ABSTRACT The Hanseatic League, a late medieval merchant association with roots in northern German towns, is credited with the establishment of extensive economic and geographic connections and considerable impact on the development of urban culture around the Baltic and the North Sea. Its merchants, regularly crossing the Seas and settling in foreign ports, created a network of diasporic communities often maintaining close physical and emotional connections with their home towns. This chapter focuses on the late medieval German diaspora in Kalmar (Sweden) and Tallinn (Estonia) and examines cultural and material practices of these communities. It theorizes about the role and meaning of everyday material culture for Hanseatic merchants and their families, and investigates how material objects figured in the experience of relocation. It discusses the centrality of everyday things in rebuilding the migrants' lives after relocation, constructing a sense of diaspora community and maintaining connections with families they left behind.